POTENSI, TANTANGAN, DAN STRATEGI PEMASARAN KOPI (Studi Kasus Usaha Pengelolaan Kopi Kelompok Wanita Tani Suka Makmur I di Dusun Ngaglik, Desa Pledokan, Kabupaten Semarang) - Maurinus Junedi Laka Senda; Tinjung Mary Prihtanti (Universitas Galuh Ciamis, 2021)
This research aims to: Analyze the potential, challenges, and marketing strategies of coffee products produced by group I of Suka Makmur woman farmers. The source of information obtained from this research came from the key informants of the marketing department and the head of the group I of Suka Makmur women farmer as an informant. The initial data collected by using the interview method, then using a questionnaire to collect more research data. The data analysis technique in this research is used IFE, EFE, IE, SWOT, and QPSM matrices. The results of this study are the group I of Suka Makmur women farmers have 12 strength factors, 5 weaknesses factors, 8 opportunities, and 2 threats factors faced by the company, and 10 alternative marketing strategies are recommended for group I of Suka Makmur women farmers.